First validation of the technical and administrative staff quality of life at work tool (TASQ@work) in academia - Bruno, Andreina; Buono, Carmela; Falco, Alessandra; Brondino, Margherita; Capone, Vincenza; Dell’Aversana, Giuseppina; Giancaspro, Maria Luisa; Gilardi, Silvia; Girardi, Damiano; Guglielmi, Dina; Ingusci, Emanuela; Miglioretti, Massimo; et al. (Frontiers in Psychology, 2024)
Based on the job demands-resources (JD-R) model, the present study aimed to validate “The Technical and Administrative Staff Quality of Life At Work” (TASQ@work), a new tool to assess the quality of life at work in academia focused on technical and administrative staff. This tool was developed by the QoL@Work research team, a group of expert academics in the field of work and organisational psychology affiliated with the Italian Association of Psychologists. The TASQ@work was elaborated in different steps. The first phase was aimed at the identification of the dimensions of the tool. The second phase was aimed to assess the psychometric properties of the tool. The validation process involved confirmatory analysis and measurement invariance of the various constructs selected. The analyses were performed in a convenience sample of two Italian universities in different regions (one in the Northwest and the second in Central Italy). The sample was composed of 1820 Administrative Staff, comprising 69.4 % from University 1 (N=1263) and 30.6 % from University 2 (N=557). The TASQ@work presented satisfactory psychometric properties (normality of the items, reliability and content, construct and nomological validity) and measurement invariance across gender, seniority, and Athenaeum. The results indicate that the tool can be considered a reliable and valid instrument to assess job demands, job resources, and outcomes in the working life of technical and administrative academic staff. In this perspective, the present study represents the first contribution to the debate on the psychosocial risks in academic contexts by presenting a new tool, the TASQ@work, aimed at contextualising the JD-R model to understand the role played by psychosocial aspects in affecting the well-being of the academic employees.